STATISTICAL CHARACTERISTICS OF HYPERBOLIC ORBITS METEORS - Markina, A. K.; Skoblikova, L. Ya. (Одеські астрономічні публікації, 2017)
We present statistical data on the distribution of orbital elements and parameters of interstellar sporadic hyperbolic meteors. We show that for some of them there is a proximity of their orbits with the Earth's orbit that can be interpreted as evidence of an existence of their interstellar